Jurnal ILMU KOMUNIKASI: MEDIA DIASPORA PELAJAR INDONESIA: EKSISTENSI, PERAN, DAN SPIRIT KEINDONESIAAN - Yohanes Widodo (PRODI Ilmu Komunikasi UAJY, 2017)
This paper discusses how Indonesian student diaspora has interacted with their peers and built their identity through media by looking at the role of Indonesian student diaspora media since pre-independence era to reform era (1900-2016).